Design thinking for entrepreneurs and small businesses : putting the power of design to work - Ingle, Beverly Rudkin (Apress, 2013)
This book is the first book on the subject for smaller businesses. Until now, design thinking - a methodology for solving business problems and identifying opportunities - has been the playground fro companies with big budgets, giving them the advantage of the innovation that comes from using the latest design thinking tools emerging from Stanford, Harvard, Northwestern and elsewhere.